2019
DOI: 10.1002/ehf2.12505
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sodium‐glucose cotransporter 2 inhibitors on left ventricular function: current evidence and future directions

Abstract: Sodium-glucose cotransporter 2 (SGLT2) inhibitors are a unique class of oral anti-hyperglycaemic medications that act to reduce glucose reabsorption in the renal proximal tubules, thereby enhancing urinary glucose excretion. Large randomized placebo-controlled trials in people with diabetes at high cardiovascular risk have demonstrated that SGLT2 inhibitors reduce heart failure hospitalization within months of commencing therapy. These findings are of considerable interest, as diabetes is associated with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 46 publications
(85 reference statements)
0
65
0
3
Order By: Relevance
“…[18] SGTL2i has been shown to reduce blood sugar levels, blood pressure, body weight, albuminuria, lipid pro le, arterial stiffness, and endothelial function via an insulin-independent mechanism in T2DM patients. [19] Moreover, SGLT2i has been shown to have impressive cardioprotective and renoprotective effects. The main mechanisms of their cardioprotective effects are improvements in cardiac cell metabolism and ventricular loading conditions, inhibition of Na + /H + exchange in myocardial cells, alterations in adipokine and cytokine production, and reductions in cardiac cell necrosis and cardiac brosis.…”
Section: Discussionmentioning
confidence: 99%
“…[18] SGTL2i has been shown to reduce blood sugar levels, blood pressure, body weight, albuminuria, lipid pro le, arterial stiffness, and endothelial function via an insulin-independent mechanism in T2DM patients. [19] Moreover, SGLT2i has been shown to have impressive cardioprotective and renoprotective effects. The main mechanisms of their cardioprotective effects are improvements in cardiac cell metabolism and ventricular loading conditions, inhibition of Na + /H + exchange in myocardial cells, alterations in adipokine and cytokine production, and reductions in cardiac cell necrosis and cardiac brosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that SGLT2 inhibitors reduced all-cause mortality [30], and other meta-analyses and systematic reviews suggested that SGLT2 inhibitors protect against CVD and death in diverse subsets of the patients with T2DM regardless of CVD history [31]. Several mechanisms through which SGLT2 inhibitors have improved cardiovascular events have been studied; however, it is unclear which mechanism is most crucial [15]. The potential effects of SGLT2 inhibitors on LV structure and function are multifaceted, and these effects may be due to effects on systemic hemodynamics and metabolism [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SGLT2 inhibitors may reduce the activation of the re ex sympathetic nervous system or implicate other neurohormonal pathways that affect the heart [34,35]. The signi cant effects of SGLT2 inhibitors on cardiovascular outcomes may also be attributed to the anti-oxidative, anti-in ammatory, or anti-apoptotic properties of SGLT2 inhibitors as shown in experimental models [15,36,37]. However, whether such effects seen in such preclinical studies affect humans remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, SGLT2is appear to have a positive impact upon left ventricular mass in the earlier phases of DMCM and improved ventricular performance (reviewed in ref 13). The ventricular remodeling and progression from HFpEF to HFrEF appear to be characterized by ischemic heart disease and ischemia/reperfusion injury, 11,12 and this too represents a target for SGLT2is.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%